Exploring perceptions of care quality, and the barriers and facilitators to implementation of a quality improvement programme at Zomba Mental Hospital, Malawi - Mwale, Owen Chapweteka (Department of Psychiatry and Mental Health, 2024)
BACKGROUND: There are different ways of describing quality of mental health services. Most institutions and researchers consider services to be of good quality when they are cost-effective, efficient, evidencebased, target specific needs of patients, and meet the expectation of users. Quality mental health services are those provided by qualified and competent providers in recognised facilities. For hospitals to know the quality of services they provide, measuring the quality of those services becomes necessary. However, measuring quality care in mental health is complex because of the involvement of many stakeholders such as doctors, patients, administrators, health insurance companies, pharmaceutical industries, and regulatory bodies. This complexity demands the need for a quality measurement framework that brings consistency, common thinking, and understanding among the team members tasked with implementing a quality improvement program. Even though many frameworks have been developed and implemented in different settings, the Donabedian quality measurement framework that focusses on structures, processes and outcomes is widely accepted and has been used to measure healthcare quality (including mental health services) in different settings (in both developed and developing countries). Designing and implementing quality improvement (QI) programs in mental health care settings needs input from patients and service providers. Furthermore, understanding the barriers and facilitators to implementing a QI program will guide an institution to use opportunities that would facilitate the process and mitigate the barriers. Many studies that explored service users’ and service providers’ perceptions of care quality and established barriers to implementing quality improvement programs have been conducted in developed countries. Few studies have been done in developing countries, including Malawi, even though several studies have reported poor quality of mental health services. This study, therefore, aimed to explore perceptions of care quality among service providers and service users and identify the barriers and facilitators to implementing a quality improvement program at Zomba Mental Hospital (ZMH) in Malawi. METHODS: This qualitative study was conducted at Zomba Mental Hospital (ZMH) which a referral government mental health facility in Malawi. The study used a purposive sampling technique and recruited nineteen participants and data saturation was achieved. Nine discharged patients (6 males and 3 IV females) who were waiting to be collected by family members and ten permanent providers (5 males and 5 females) were interviewed. Health care providers interviewed included: 3 psychiatric clinical officers, 2 nursing officers, 2 psychiatric nurses, 1 nurse midwife technician, and 2 patient attendants. Individual in-depth interviews were conducted in English for providers and local language Chichewa for the patients by the researcher using a semi-structured interview guide. The English language interviews were transcribed by a PhD student, while the Chichewa language interviews were translated into English before being transcribed by a research assistant who holds a Bachelor’s degree and has experience in transcribing qualitative data. The transcribed data were analysed using both inductive and deductive thematic analyses. While the deductive approach maintains a link between the results of the study and its objectives, the inductive approach allows the themes to emerge from the data themselves. RESULTS: Categorisation of perceptions of the quality of mental health services among service providers (members of staff) and service users (discharged patients) was based on the Quality Improvement (QI) framework: structures, processes of care and outcomes. The results showed more similarities than differences in the way discharged patients and members of staff perceived the quality of care at the hospital and this resulted in identifying common themes. Both positive and negative perceptions on quality of services at ZMH were found from both groups. The following themes were identified on perception of quality care at ZHM: Availability and comprehensiveness of services at outpatient department, design and ward environment (acute and rehabilitation), resources (human and material), use of seclusion rooms spaces and single rooms, patient assessment process, treatment and medical procedures (drug administration, nursing care, occupational therapy and ward rounds), free mental health services and food, and effective treatment (recovery outcomes). The perceived barriers to implementing a QI program included heavy staff workload, lack of knowledge and commitment, lack of motivation, limited resources, and resistance to change. Facilitators to QI programmes included training, availability of resources, teamwork, staff motivation, positive attitudes, innovations and collaborations, and a committed management team. CONCLUSION: The findings on perceived care quality, barriers and facilitators to implementing QI programs from services users and service providers offers an opportunity for ZMH management to establish evidencebased improvement programs at the facility. These findings are in line with some previous studies at V the facility that focused on specific issues such as medication side effects, patient welfare and nutritional status of the patients.